2018
DOI: 10.1021/acs.jpcb.8b01420
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Loading Sulfur Hexafluoride in γ-Cyclodextrin Metal–Organic Framework

Abstract: γ-Cyclodextrin metal-organic framework (γ-CD-MOF) is a new type of highly porous carrier for potential loading of therapeutic or diagnostic gas like sulfur hexafluoride (SF). Here, loading of SF into γ-CD-MOF was investigated for its mechanism by molecular simulation and quantitative determination of SF using quantitative nuclear magnetic resonance (qNMR). For the SF loading, γ-CD-MOF was first degassed to remove the air without thermal decomposition or loss of framework crystallinity, then placed in the coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Previous studies have shown that hydrogen bonding is important for stabilising host−guest inclusion. 51 The molecular docking study of azilsartan/γ-CD-MOFs and folic acid/γ-CD-MOFs also showed similar preferential binding sites. 43,52 Furthermore, due to the limited size of the nanocavities inside γ-CD-MOFs, the guest molecules appeared to be chaotic and formed stable nanoclusters, which could not grow further into a large insoluble particle.…”
Section: Molecular Docking Of Que and Cd-mofsmentioning
confidence: 85%
“…Previous studies have shown that hydrogen bonding is important for stabilising host−guest inclusion. 51 The molecular docking study of azilsartan/γ-CD-MOFs and folic acid/γ-CD-MOFs also showed similar preferential binding sites. 43,52 Furthermore, due to the limited size of the nanocavities inside γ-CD-MOFs, the guest molecules appeared to be chaotic and formed stable nanoclusters, which could not grow further into a large insoluble particle.…”
Section: Molecular Docking Of Que and Cd-mofsmentioning
confidence: 85%
“…The binding energy was found to be −12.8, kcal/mol. for Cu‐BTC with Rif and −9.0 kcal/mol for MIL‐100 (Fe) with Rif [56–58] …”
Section: Resultsmentioning
confidence: 99%
“…Formaldehyde can be adsorbed through the hydrogen bonding of the hydroxyl group in γ-CD-MOFs [21]. γ-CD-MOF can also be used to adsorb sulfur hexa uoride, and the packaging capacity can reach 2.7 ± 0.5% (w/w) after 12 hours of treatment at 1.2 MPa [22]. Al-Ghamdi et al (2016) used γ-CD-MOF for acetaldehyde adsorption, and its adsorption capacity can be as high as 53 µg/g [23].…”
Section: Introductionmentioning
confidence: 99%